Drug Development for Alzheimer's Disease: Where Are We Now and Where Are We Headed? - Sabbagh, Marwan N. (2009)
OBJECTIVE: To provide a brief survey of the clinical development of Alzheimer's disease (AD) pharmacotherapy. METHODS: The search process included PubMed, www.ClinicalTrials.gov, the International Conference on Alzheimer's Disease 2008 (ICAD), and pharmaceutical company and AD advocacy Web sites. Selected articles were primary manuscripts reporting clinical trial or preclinical study results in English in peer-reviewed journals. RESULTS: The AD pipeline comprises a large number of drugs with differing targets and mechanisms of action. No novel agent, since the approval of memantine in 2002, has successfully completed a phase 3 trial however, encouraging phase 2 results were reported for several compounds at ICAD 2008, and the overall number and variety of novel agents in clinical development continues to expand. CONCLUSIONS: Despite clearly disappointing results of recently completed phase 3 trials for several leading novel compounds, the breadth and depth of the clinical development pipeline at all phases of development provides ample justification to expect that new pharmacotherapeutic options will become available for the treatment of AD within the next 3 to 5 years. Nonetheless, it is not yet clear which agent or therapeutic strategy will be the next to be approved for clinical use. In the meantime, it is important to not underestimate the value of currently available treatments, and to ensure that every patient with AD is prescribed optimal pharmacotherapy as early in the course of the disease as possible.